The roles of HOXB7 in promoting migration, invasion, and anti‐apoptosis in gastric cancer. Issue 10 (October 2016) - Joo, Moon Kyung; Park, Jong‐Jae; Yoo, Hyo Soon; Lee, Beom Jae; Chun, Hoon Jai; Lee, Sang Woo; Bak, Young‐Tae
Abstract: Background and Aim: The aim of this study was to compare HOXB7 expression level between gastric cancer and non‐cancerous gastric tissues. Additionally, the functional effects of HOXB7, including its pro‐migration or invasion and anti‐apoptosis roles, were evaluated in gastric cancer cells. Methods: Both gene and protein expression levels of HOXB7 were examined in gastric cancer cell lines, and HOXB7 expression was compared between primary or metastatic gastric cancer tissues and chronic gastritis or intestinal metaplasia tissues. Functional studies included a wound healing assay, a Matrigel invasion assay, and an Annexin‐V assay were performed, and Akt/PTEN activity was measured by western blotting. Results: Both gene and protein expression levels of HOXB7 could be clearly detected in various gastric cancer cell lines except MKN‐28 cell. HOXB7 expression was significantly higher in primary or metastatic gastric cancer tissues than in chronic gastritis or intestinal metaplasia tissues. HOXB7 knockdown led to inhibition of cell invasion and migration, had an apoptotic effect, downregulated phosphor‐Akt, and upregulated PTEN in AGS and SNU‐638 cells. Reinforced expression of HOXB7 caused the opposite effects in MKN‐28 and MKN‐45 cells. Conclusion: Our study suggests that HOXB7 has an oncogenic role in gastric cancer, which might be related to the modulation of Akt/PTEN activity to induce cell migration/invasion and anti‐apoptotic effects.